Effects of reinforcement corrosion on reinforced concrete buildings - Yüksel, İsa; Sakcalı, Gökhan Barış (ICE Publishing, 2022)
The aim of this paper is to present the different effects of reinforcement corrosion on reinforced concrete buildings. A hypothetical five-storey reinforced concrete building frame was designed for this purpose. Three different modes of action were selected - corrosion on the ground floor alone, corrosion on one facade and corrosion on two neighbouring facades of the building. For each mode of action, different corrosion scenarios were selected, which were arranged in terms of mass loss from zero to 15% in ascending order an in 3% steps. Pushover analyses of the building were performed for each corrosion scenario and the results of these analyses were used to perform a structural performance evaluation conforming to Eurocode 8. A general decrease in structural performance was determined with significant changes in the dynamic characteristics of the building. The level of decrease depended on the corrosion scenarios and the modes of action. Important structural behaviour alterations and premature damage occurrences were found, in addition to a reduction in the displacement ductility of the building. For severe-corrosion scenarios, reductions in moment and curvature capacities could shift the structural behaviour of the load-bearing members from ductile to non-ductile.
Keywords: Concrete structures; Corrosion; Structural frameworks